READINESS OF TEACHING AND LEARNING ENGLISH AT ELEMENTARY SCHOOLS IN MATARAM CITY - Lalu Suhirman (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
This research is aimed at describing the readiness of teaching-learning English at elementary school (ES) in Kodya Mataram, accentuating on perception of respondents; English teacher’s qualifications; the availability of English techer and teaching facility; students’ interest of study English; and constrains in English instruction. This survey assigns its subjects to 14 principals without EP, 49 parens of children’s schools with EP, and 55 parents of children’s schools without EP. The instruments used to collect data are questionnaire, interview guide, and observation form. The study reveals that (1) most respondents in each group are ready to teach English at ES; (2) English teachers’ qualification meet the criteria; (3) Of 30 ES without EP, 7 (23.33%) are ready, English text books for ES with are categorized mostly ready; and (4) Students at ES with are mostly ready. In addition, 9 (30%) of students at 30 non-ESP schools are totally not ready.